Book Review; Menjadi Saintis Muslim - Shohib Khoiri (Jurnal Sosioteknologi, 2020)
Book Title                   :Menjadi Saintis IslamAuthor                         : Usep Mohamad Ishaq, Ph.DPublisher                     : Indie Publishing, Depok IndonesiaPublishing Year          : 2014ISBN                           : 978-602-281-089-6Pages                           : 209Genre                          : Scientific Book